Effectiveness of Contextualized Teaching Strategies in Mathematics for Grade Six Pupils - Malsi, Jn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of contextualized teaching strategies in improving the Mathematics performance of Grade Six pupils at Muzon Elementary School, Taytay District, Division of Rizal, during the School Year 2025–2026. Specifically, it compared the academic performance of pupils exposed to contextualized teaching strategies and those taught using the traditional method, while also examining whether selected demographic variables influenced learning outcomes. The study employed an experimental research design using a parallel-group approach involving ninety-five (95) Grade Six pupils, with fifty (50) assigned to the experimental group and forty-five (45) to the control group. A validated 50-item teacher-made Mathematics achievement test was administered as both pretest and posttest to measure pupils' performance before and after the intervention. Data were analyzed using appropriate descriptive and inferential statistical tools. Findings revealed that both groups obtained a Satisfactory level of performance during the pretest. Following the intervention, the control group maintained a Satisfactory rating, whereas the experimental group improved to a Very Satisfactory level. Statistical analysis indicated significant differences in the pretest and posttest performance between the experimental and control groups, demonstrating that contextualized teaching strategies contributed to greater improvement in Mathematics achievement than the traditional method. Furthermore, no significant differences were found in the posttest performance of pupils in the experimental group when grouped according to sex, sibling position, number of children in the family, monthly family income, and parents' educational attainment, indicating that these variables did not significantly influence learning outcomes after exposure to contextualized instruction. The study concluded that while both instructional approaches enhanced pupils' performance, contextualized teaching strategies produced greater gains in Mathematics achievement by making learning more meaningful and relevant to pupils' real-life experiences. It is therefore recommended that school administrators support the implementation of contextualized teaching through adequate instructional resources and professional development, while teachers continuously integrate contextualized strategies, conduct regular learning assessments, provide appropriate interventions, and sustain learner-centered instructional practices to further improve Mathematics performance
Keywords: Contextualized Teaching Strategies, Mathematics Achievement, Grade Six Pupils, Experimental Research, Contextualized Learning, Traditional Teaching Method, Mathematics Education